Strategi Pemasaran Vitoza Madu Pahit di Tiktok melalui Konten Komedi Situasional - Nadia Arta M; Vivien Febri Astuti (ALAMTARA, 2025)
Previous studies on comedic content on TikTok have generally focused on its impact on audience engagement, while research examining the content production process as a marketing strategy remains limited. This study aims to analyze the production process of situational comedy content as a marketing strategy for Vitoza Madu Pahit on TikTok. A qualitative descriptive approach was employed through field observation, active participation, interviews, and literature review. The findings indicate that the production of situational comedy content is carried out through structured yet adaptive stages of pre-production, production, and post-production in response to digital trends. The success of the marketing strategy is influenced by internal factors such as teamwork, communication, and leadership, as well as external factors including social media trends and audience responses. This study highlights the importance of the creative content production process as a strategic element in social media–based digital marketing.